The devil's bed eaudiobook - Krueger, William Kent (Recorded Books, 2014)
From the creator of the critically acclaimed, award-winning Cork O'Connor mystery series comes a haunting, atmospheric, conspiracy thriller. When President Clay Dixon's father-in-law—a former vice president—is injured in a farming accident, First Lady Kate Dixon returns to Minnesota to be at his side. Assigned to protect her, Secret Service agent Bo Thorsen soon falls under Kate's spell. He also suspects the accident is part of a trap set for Kate by David Moses, an escaped mental patient who once loved her. What Bo and Moses don't realize is that they're caught in a web of deadly intrigue spun by a seemingly insignificant bureaucratic department within the federal government. Racing to find answers before an assassin's bullet can kill Kate, Bo soon learns that when you lie down with the devil, there's hell to pay.